Methoxydioxasilepane: A Versatile and Stable Synthetic Precursor of Trimethoxysilane - Hitoshio, Kenshiro; Morinaga, Takuto; Sahashi, Ryohei; Goshona, Shinya; Yamagishi, Hiroki; Saito, Hayate; Shimokawa, Jun; Yorimitsu, Hideki (Synthesis, 2024)
This study introduces aryl(methoxy)dioxasilepane as a versatile and stable precursor for aryl(trimethoxy)silanes. We conducted a quantitative assessment of the stability of this silicon moiety under acidic and basic conditions, demonstrating its superior stability compared to triethoxysilane, and methyl- or (trifluoroethoxy)dioxasilepanes. The synthetic utility of the methoxydioxasilepane unit was further elucidated through an examination of its orthogonality and selective functionalization capabilities. Notably, we developed an efficient method for the conversion of methoxydioxasilepane into trimethoxysilane. This method underscores the potential of a methoxydioxasilepane as a surrogate in multistep syntheses of silanetriols, which offer advantages in the development of silicon-based bioisosteres for medicinal chemistry applications.
Keywords: silanols; silanetriols; alkoxysilanes; bioisosteres; dioxasilepanes